ตัวแปรที่สัมพันธ์กับการยอมรับเทคโนโลยีคอมพิวเตอร์ ของครูโรงเรียนประถมศึกษา สังกัดสำนักงานคณะกรรมการการประถมศึกษาแห่งชาติ เขตการศึกษา 11 - พัชราภรณ์ ผางสระน้อย (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
To study the adoption of computer technology of elementary school teachers under the jurisdiction of the National Primary Education Commission, educational region 11; to study the relationships between the adoption of computer technology of elementary school teachers and three categories of selected variables: teacher socioeconomic characteristics, roles of administrators, supervisors, academic teachers of elementary school clusters, colleagues as change agents in diffusion of computer technology, and perception of computer technology characteristics; and to identify predictor variables in the adoption of computer technology. The samples were 370 elementary school teachers under the jurisdiction of the National Primary Education Commission, educational region 11. The findings revealed that : 1. The elementary school teachers under the jurisdiction of the National Primary Education Commission, educational region 11 adopted computer technology in moderate level. 2. There were statistically significant positive relationships at .01 level between the adoption of computer technology in five stages and 67 selected variables. The first three variables were : computer as learnable innovation, computer appropriate for work responsibilities and computer appropriate as instruction media. There were statistically significant negative relationship at .01 level between the adoption of computer technology in five stages and 4 selected variables were : 51 - 60 years of age, large-size school, over 16 years of teaching experiences, education level lower than bachelor degree. 3. In multiple regression analysis (Enter Method) at .01 level, in knowledge stage, persuasion stage, decision stage, implementation stage, and confirmation stage, there were 1, 3, 4, 2, 3 predictor variables together were able to account for 58.77%, 72.02%, 61.11%, 61.01% and 62.79% of the variance. The variables found in four stages were computer appropriate for work responsibilities. 4. In stepwise multiple regression analysis at .01 level, in knowledge stage, persuasion stage, decision stage, implementation stage, and confirmation stage, there were 9, 8, 6, 6, 7 predictor variables together were able to account for 46.57%, 63.78%, 45.76%, 48.91% and 51.99% of the variance. The variables found in five stages were computer as learnable innovation and computer appropriate for work responsibilities.